Conversations with Beth Henley - Bryer, Jackson R.; Hartig, Mary C. (Literary conversations series., 2023)
"With roots in the American South, Beth Henley (b. 1952) has for four decades been a working playwright and screenwriter. Winner of the Pulitzer Prize in 1981 at the age of twenty-eight, Henley so far has written twenty-five produced plays that are always original, usually darkly comic, and often experimental. In these interviews, Henley speaks of the plays, from her early crowd-pleasers, Crimes of the Heart and The Miss Firecracker Contest, to her more experimental plays, including The Debutante Ball and Control Freaks, to her brilliant and time-bending play, The Jacksonian. Henley is a master at writing about the duality of human experience-the beautiful and the grotesque, the cruel and the loving. This duality provokes in Henley both amazement and compassion. She discusses here not only her admiration for Chekhov and other influences, but also her process of bringing a play from notebooks of images and bits of dialogues through rumination, writing, and rewriting to rehearsals and previews. The interviews range from 1981, just before she won the Pulitzer Prize, to 2020 and cover nearly forty years of a creative life, which, as Henley remarks in the most recent interview, is "such a life worth living: to be in tune with the creative process.""--